Sociology of Shi'ite Islam : collected essays - Arjomand, Said Amir. (Middle East and Islamic Studies E-Books Online, Collection 2017, ISBN: 9789004325999., 2016)
Sociology of Shiʿite Islam is a comprehensive study of the development of Shiʿism. Its bearers first emerged as a sectarian elite, then a hierocracy and finally a theocracy. Imamate, Occultation and the theodicy of martyrdom are identified as the main components of the Shiʻism as a world religion. In these collected essays Arjomand has persistenly developed a Weberian theoretical framework for the analysis of Shiʿism, from its sectarian formation in the eighth century through the establishment of the Safavid empire in the sixteenth century, to the Islamic revolution in Iran in the twentieth century. These studies highlight revolutionary impulses embedded in the belief in the advent of the hidden Imam, and the impact of Shiʻite political ethics on the authority structure of pre-modern Iran and the constitution of the Islamic Republic of Iran.